Determinants of the Capital Structure and Investment Strategies in Fintech Companies: A Comparison of Developing vs Developed Countries - Pinheiro, Erikson Rosamonte (Digital Repository of Theses, 2024)
This study aims to identify the differences between developing and developed country firms concerning country-level determinants of capital structure. For this purpose, this study considers the theories of capital structures and evaluates the support of developing and developed country firms for the Pecking order and the Trade-off theory. However, the capital structure determinants have been evaluated and determined the connections between theory and how developed and developing country firms make their financing decisions. The quantitative approach and data collection method were implemented for capital structure determinants based on the literature review and theories. The data was collected over 7 years between 2015 to 2021 and amounted to 250 firms. The study employed Hausman-Taylor regression to demonstrate the impact of debt ratio and long-term debt on the financial outcomes of developing and developed country firms to get a better understanding of the results. Analysis of the results determined that the debt ratio of developing country firms had a significant negative relationship with GDP growth while long-term debt had impacted the risk-free rate negatively and inflation positively. This indicates that developing country firms need to finance their business operations with internal funds instead of using the debt that supports the Pecking Order theory. The developed country firms’ debt ratio did not impact the GDP, inflation, risk-free rate, and share market return. The study findings evaluated that the macro environment of developing country firms’ long-term debt is reduced with the reduced inflation that potentially demonstrated the higher interest rates and unwillingness to finance debt with the increased cost of financial distress. The study also considered that the companies in developing countries have gradually become less leveraged across the world after the COVID-19 pandemic compared to the developed countries’ firms. This study provides a new perspective into the capital structure determinants and their impacting differences between developing and developed country firms based on debt-equity ratio, long-term debt, risk-free rate, inflation, GDP, investment, and share-market return.